The effects of time-restricted eating on sleep in adults: a systematic review of randomized controlled trials - Bohlman, Carly; McLaren, Christian; Ezzati, Armin; Vial, Patricia; Ibrahim, Daniel; Anton, Stephen D. (Frontiers in Nutrition, 2024)
Time-restricted eating (TRE), a dietary pattern reducing the duration of daily food consumption, has recently gained popularity. Existing studies show the potential benefits of TRE for cardiometabolic health. Uncertainty remains about whether these benefits are solely from altered meal timing or influences on other health behaviors, including sleep. Despite growing scientific interest in the effects of TRE on sleep parameters, the topic has not been systematically explored. Thus, this review examined the effects of TRE interventions (daily fasting duration > 14 hours) lasting at least eight weeks on objective and subjective sleep parameters. Six randomized control trials were identified through Pubmed, Embase, Google Scholar, and Scopus through September 2023. Of the included studies, three employed objective sleep measures using wearables and five studies assessed sleep subjectively through self-report questionnaires. Only one study reported significant improvements in subjective sleep quality following a TRE intervention. Additionally, one study found significant decreases in sleep duration, two studies found significant decreases in sleep efficiency, and one found significant increases in sleep onset latency. Current evidence indicates that short to mid-term TRE does not typically worsen sleep parameters. However, some populations may experience reduced sleep disturbances, while others may experience reductions in sleep efficiency. Longer duration studies with objective sleep assessments are needed to better understand the effects of TRE on sleep parameters.